Landslide Failure Mechanisms of Dispersive Soil Slopes in Seasonally Frozen Regions - Lixiang Wang; Xiaoming Yuan; Miao Wang (Advances in Civil Engineering)
Hydraulic projects with dispersive soil in seasonally frozen regions are susceptible to landslide failures. The mechanism of such landslide failures has not been fully understood thus far; therefore, it was investigated in this study by using on-site surveys, laboratory tests, and theoretical calculations. The results showed that the landslides of dispersive soil in seasonally frozen regions could be categorized as shallow-seated landslides and deep-seated landslides. The preconditions for landslide occurrence were soil mass looseness and cracks, caused by freeze-thawing. The degradation of dispersive soil led to a rapid influx of water into the soil. The reason for shallow-seated landslides was that the numerous sodium ions present in the soil mass dissolved in water and damaged the soil structure, resulting in a substantial reduction in shear strength. The reason for deep-seated landslides, however, was the erosion due to rainfall infiltration after the shallow-seated landslides caused tensile cracks at the top of the slope, leading to soil instability. Landslide failures occurred when the dispersing soil slope underwent freeze-thawing and saturated soaking. The sliding surface was initiated at the top of the slope and gradually progressed to the bottom along the interface between the soil layers.